Effect of rice straw powder on properties of one-part alkali-activated slag - Yin, Kangting; Jiang, Yaqing; Wang, Yu; Zhao, Wenhao; Pan, Zhenghua; Li, Zhenming (Frontiers in Built Environment, 2022)
One-part alkali-activated slag (AAS) as a binder material has a promising application in construction industry. The properties of one-part AAS incorporating agricultural wastes have been seldom studied. In this paper, the fresh and hardened properties of one-part AAS with the addition of rice straw powder (RSP) were investigated. The reaction rate in the acceleration period of AAS is reduced by RSP. The compressive strength of the mixture decreases with the introduction of RSP, while the flexural strength increases. The porosity of the hardened mixtures becomes lower when RSP was incorporated. N-(C)-A-S-H gel was detected in the system when 4.2% RSP is present. The RSP reduces the early-age autogenous shrinkage of AAS by providing internal curing to the matrix, but its effect on long-term drying shrinkage is limited.